2020
DOI: 10.1016/j.biomaterials.2019.119559
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of CSF1R and MAPK pathways using supramolecular nanoparticles enhances macrophage immunotherapy

Abstract: Among the numerous immune interactions, or lack-thereof, that occur during cancer progression, tumor-associated macrophages (TAMs) -cancer cell interactions have been shown to play an important role in modulating the tumor-microenvironment to an immune suppressive mode, promoting accelerated tumor growth, survival and metastatic spread. TAMs are predominantly polarized to a pro-tumorigenic M2-phenotype through macrophage colony stimulating factor 1 (MCSF) cytokines that bind to the colony-stimulating factor 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 42 publications
(52 reference statements)
2
65
0
Order By: Relevance
“…Patients with high-risk scores are mainly enriched in the complement and coagulation cascades, ECM receptor interaction, focal adhesion, hedgehog signaling pathway, MAPK signaling pathway, notch signaling pathway, pathways in cancer, and Wnt signaling pathway ( Figure 5A). Studies have reported that these pathways are closely related to the immune process (Gao et al, 2019;Hanna et al, 2019;Ramesh et al, 2019;Yang et al, 2019). Patients with low-risk scores are mainly enriched in terpenoid backbone biosynthesis, steroid biosynthesis, porphyrin and chlorophyll metabolism, and the citrate cycle ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high-risk scores are mainly enriched in the complement and coagulation cascades, ECM receptor interaction, focal adhesion, hedgehog signaling pathway, MAPK signaling pathway, notch signaling pathway, pathways in cancer, and Wnt signaling pathway ( Figure 5A). Studies have reported that these pathways are closely related to the immune process (Gao et al, 2019;Hanna et al, 2019;Ramesh et al, 2019;Yang et al, 2019). Patients with low-risk scores are mainly enriched in terpenoid backbone biosynthesis, steroid biosynthesis, porphyrin and chlorophyll metabolism, and the citrate cycle ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlight the fact that therapies that target TAMs to achieve anticancer efficacy by functional reprogramming of immunosuppressive M2 TAMs need to rely on strategies that can repolarize “M2‐like” TAMs to “M1‐like” TAMs efficiently and in a sustained manner. [ 25–27 ] Classically activated M1 macrophages activate the Th1 immune response to secrete high amounts of proinflammatory cytokines that induce tumor cell killing, such as tumor necrosis factor (TNF), IL‐12, and nitric oxide (NO). [ 28 ] Highly inducible nitric oxide synthase production, a precursor for nitric oxide production, is indicative of inflammatory response and it has been well established that gaseous nitric oxide secreted by macrophages in the tumor microenvironment aids in arresting cell cycle and inhibiting tumor progression.…”
Section: Figurementioning
confidence: 99%
“…In our previous studies, we have shown that stable lipid‐based supramolecular nanoparticles can be formed by self‐assembly of colipids (phosphatidylcholine, 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐ N ‐[amino(polyethylene glycol)‐2000] (DSPE–PEG‐2000)–amine, and amphiphilic drug–cholesterol conjugate) facilitated by hydrophilic and hydrophobic interactions. [ 25–27,45,46 ] Previous studies have also validated the efficacy of these supramolecular nanoparticles encapsulated with small molecule inhibitors involved in macrophage modulation, in eliciting antitumoral responses, due to its sustained drug release capabilities that resulted in sustained inhibition of intracellular signaling pathways. [ 27 ] Hence, we rationalized that these lipid‐based supramolecular nanoparticles would be ideal carriers in terms of enhanced delivery of the NO probe to tumor‐associated macrophages.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The same study group showed that nanotechnology can also be used to modulate tumor microenvironment together with kinase inhibition [49]. Supramolecular nanoparticles were used to inhibit colony-stimulating factor 1 receptor (CSF1R) and MAPK signaling and to further block the pro-tumorigenic phenotypes of tumor-associated macrophages [49]. They also detected a significant macrophage repolarization towards an anti-tumorigenic phenotype [49].…”
Section: Molecularly Targeted Therapymentioning
confidence: 99%